A novel integrated cytogenetic and genomic classification refines risk stratification in pediatric acute lymphoblastic leukemia. - Moorman, A; Enshaei, A; Schwab, C; Wade, R; Chilton, L; Elliott, A; Richardson, S; Hancock, J; Kinsey, SE; Mitchell, C; Goulden, N; Vora, A; et al. (American Society of Hematology, 2014)
Recent genomic studies have provided a refined genetic map of acute lymphoblastic leukemia (ALL) and increased the number of potential prognostic markers. Therefore, we integrated copy-number alteration data from the 8 most commonly deleted genes, subordinately, with established chromosomal abnormalities to derive a 2-tier genetic classification. The classification was developed using 809 ALL97/99 patients and validated using 742 United Kingdom (UK)ALL2003 patients. Good-risk (GR) genetic features included ETV6-RUNX1, high hyperdiploidy, normal copy-number status for all 8 genes, isolated deletions affecting ETV6/PAX5/BTG1, and ETV6 deletions with a single additional deletion of BTG1/PAX5/CDKN2A/B. All other genetic features were classified as poor risk (PR). Three-quarters of UKALL2003 patients had a GR genetic profile and a significantly improved event-free survival (EFS) (94%) compared with patients with a PR genetic profile (79%). This difference was driven by a lower relapse rate (4% vs 17%), was seen across all patient subgroups, and was independent of other risk factors. Even genetic GR patients with minimal residual disease (>0.01%) at day 29 had an EFS in excess of 90%. In conclusion, the integration of genomic and cytogenetic data defines 2 subgroups with distinct responses to treatment and identifies a large subset of children suitable for treatment deintensification.